2005
DOI: 10.1002/pbc.20299
|View full text |Cite
|
Sign up to set email alerts
|

Whole body hyperthermia in adjuvant therapy of children with renal cell carcinoma

Abstract: Whole body hyperthermia (WBH) in combination with chemotherapy has been proven to be effective in some patients with advanced malignancies. However, only limited experience exists regarding the application of WBH with chemotherapy in children. We present the results of applying WBH and chemotherapy in five children with advanced renal cell carcinoma (RCC). WBH (3 hr, 41.8-42.5 degrees C) combined with doxorubicin (50 mg/m2) and interferon-alpha (3 MU/m2) were applied to patients after nephrectomy and lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…Nonetheless, there are multiple case reports of adjuvant therapy for distant metastatic disease. IsmailZade and colleagues [42] reported that a regimen of whole body hyperthermia, doxorubicin, and interferon alpha (IFNa) was tolerated by five patients, two of whom had metastatic RCC; survival in the Mþ patients was 100% with a mean follow up of 12 months. Complete responses of pediatric RCC to high dose IL-2 have been reported [43].…”
Section: Treatmentmentioning
confidence: 98%
“…Nonetheless, there are multiple case reports of adjuvant therapy for distant metastatic disease. IsmailZade and colleagues [42] reported that a regimen of whole body hyperthermia, doxorubicin, and interferon alpha (IFNa) was tolerated by five patients, two of whom had metastatic RCC; survival in the Mþ patients was 100% with a mean follow up of 12 months. Complete responses of pediatric RCC to high dose IL-2 have been reported [43].…”
Section: Treatmentmentioning
confidence: 98%
“…Improvement of local control by hyperthermia combined with systemic chemotherapy was observed by many researchers. [309][310][311][312][313][314][315][316][317][318][319] There is insufficient information to make conclusions regarding the use of WBH as an adjunct to either radiation or chemotherapy, and inadequate data regarding the use of local hyperthermia in conjunction with chemotherapy alone. This practice is based, in part, on an initial body of evidence consisting of phase I and II clinical studies describing the technical feasibility of WBH.…”
Section: B Hyperthermia and Chemotherapymentioning
confidence: 99%
“…-3-летний опыт лечения ПКР с метастатическим поражением у 14 пациентов; R. S. Ismail-zade и соавт. -способ ле-чения ПКР с помощью гипертермии у 5 детей, среди которых 2 пациента имели метастатическое пораже-ние [3,[5][6][7].…”
Section: Introductionunclassified
“…-3-летний опыт лечения ПКР с метастатическим поражением у 14 пациентов; R. S. Ismail-zade и соавт. -способ ле-чения ПКР с помощью гипертермии у 5 детей, среди которых 2 пациента имели метастатическое пораже-ние [3,[5][6][7].Данное заболевание в равной степени встречает-ся у детей обоих полов [8], в отличие от взрослых, у которых оно преобладает у мужчин. Наиболее рас-пространенные формы проявления ПКР у детей -макрогематурия и боль в боку, менее частые симпто-мы -синдром пальпируемой опухоли в брюшной полости, анемия и лихорадка [4,8].…”
unclassified
See 1 more Smart Citation